2013
DOI: 10.1002/lsm.22190
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial application of near‐infrared low‐level laser can modulate cortical excitability

Abstract: TLS with NIR-LLL induced transitory reduction of the excitability of the stimulated cortex. These findings give further insights into the mechanisms of TLS effects in the human cerebral cortex, paving the way for potential applications of TLS in treatment of stroke and in other clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 30 publications
1
33
0
1
Order By: Relevance
“…Many authors who conducted both experimental and clinical studies on extracranial laser effects on the brain [13][14][15][16][17][39][40][41][42] confirm neuroprotective effect of laser energy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many authors who conducted both experimental and clinical studies on extracranial laser effects on the brain [13][14][15][16][17][39][40][41][42] confirm neuroprotective effect of laser energy.…”
Section: Discussionmentioning
confidence: 96%
“…This process causes the development of long-term chronic ischemia leading to slowly growing neurodegenerative and atrophic changes of transcranial laser radiation in the treatment of the consequences of ischemic stroke [13,14], cranial trauma and dementia [15][16][17]. These studies indicate a good neuroprotective effect of the treatment contributing to successful neurorehabilitation, but it should be noted that these treatments are also effective in the early, not severe stages of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The neuroprotective effect of laser energy is confirmed by many authors who conducted experimental and clinical research on extracranial laser impact on the brain with different neurodegenerative lesions (Hashmi et al, 2010;Naeser et al, 2011;Konstantinović et al, 2013;Barrett et al, 2013;Yang et at., 2010).…”
Section: Discussionmentioning
confidence: 78%
“…Concerning healthy subjects, beneficial cognitive and emotional effects had been reported following frontal N-LLT. [11,12] Regarding the issue of skull penetration, Jagdeo et al had reported that near infrared measurably penetrated soft tissue, bone and brain parenchyma in the formalin preserved human cadaveric model. [13] With the transfrontal application one should keep in mind the variable size of the frontal sinus, the bone around the sinus is thicker, and not seldom a sinusitis affects severely affected chronic patients.…”
Section: Discussionmentioning
confidence: 99%